METAMORPHIC AND TECTONIC EVOLUTION OF THE HWACHEON GRANULITE COMPLEX, CENTRAL KOREA: COMPOSITE P-T PATH RESULTING FROM TWO DISTINCT CRUSTAL-THICKENING EVENTS - Lee S.R.; Cho M. (My University, 2003)
The Hwacheon granulite complex (HGC), occupying the northeastern margin of the Gyeonggi massif, consists mainly of garnetferous leucocratic gneiss and leucogranite together with minor kyanite-garnet gneiss, aluminous gneiss, mafic granulite and garnet amphibolite. Mineral assemblages and reaction textures in various rock types of the HGC document five distinct metamorphic stages: pre- (M-1) and peak (M-2) granulite-facies metamorphism; lower temperature, high (M-3) and low (M-4) pressure upper amphibolite-facies metamorphism; and local retrogression (M-5) producing andalusite-bearing assemblages. Each metamorphic stage can be integrated to give a composite, P-T path consisting of two distinct trajectories, characterized by clockwise P-T loops at relatively high and low temperatures, respectively. The first P-T trajectory (M-1-M-3) corresponds to a Palaeoproterozoic tectonometamorphic event responsible for the formation of the granulite complex at similar to 1.87 Ga. Rare inclusions of kyanite in M-2 garnet from pelitic granulites suggest an episode of crustal thickening (M,) before M, The peak granulite-facies metamorphism at similar to 7.0-9.5 kbar and 790-830degreesC induced widespread partial melting in pelitic granulites and produced syn- to post-tectonic, (para-)autochthonous leuco-granites. An episode of quasi-isobaric cooling (M-3) following the M-2 event is apparent from the occurrence of garnet coronas around orthopyroxene in mafic granulites and kyanite replacing sillimanite in pelitic granulites. The heat required for granulite formation is attributed to the burial of sedimentary protoliths rich in radiogenic elements during the Palaeoproterozoic crustal-thickening event. The second P-T trajectory (M-4) is correlated with the final exhumation of the HGC. This decompressional process, probably initiated in the kyanite stability field, reached pressures of similar to 3-6 kbar at 660-750degreesC. The clockwise P-T path may reflect the exhumation of a deep-seated crustal segment along discrete, ductile shear bones during the Permo-Tiassic collisional orogeny prevalent in-Far-East Asia.
Keywords: crustal thickening; granulite; Gyeonggi massif; Korea metamorphism; Mesozoic::Triassic; Мезозой::Триасовая; Докембрий::Протерозой::Палеопротерозойская; Paleozoic::Permian; Палеозой::Пермская; Precambrian::Proterozoic::Paleoproterozoic